The analysis of activity of the construction organizations based on studying of profit indicators - A. V. Sharkova; T. I. Chinaeva; A. S. Klepackaya (Статистика и экономика, 2018)
The aim of research. Construction belongs to one of types of economic activity and key industry, thereby having significant effect on economy and growth of well-being of nation and its economic entities. However, the crisis conditions of the last few years could not but affect the construction activity. In this regard, the analysis of the existing situation in the sphere of construction and studying of the factors, influencing increase in efficiency of activity of the construction organizations is a relevant task. The goal of this article is to study and analyze construction area by studying individual organizations, which were chosen in database “SPARK”. One of the most important quality indicators, characterizing the organization’s activities is profit, which is the final financial result and allows replenishing the organization’s financial resources. The work has evaluated the effectiveness of the formation and use of profits of the analyzed organizations, identifying existing problems. The profit is a factor that determines productivity of organization, its liquidity, ability to pay, financial sustainability in the modern market. A part of research performs economics and statistics analysis of main economic indicators, characterizing the formation and use of profit in organizations of the construction industry, and financial activity analysis of the two largest construction organizations in part of profit formation and its use.Materials and methods. Informational background is statistical data and analytical information about financial activity of construction organizations. Methodological basis of the research is statistical methods of data analysis: comparative and dynamical analysis, variational analysis, correlation and regression analysis.Results. The role of construction area in economics of Russia was analyzed. Construction is the key industry that influences the formation of the national economy. Main indicators that describe efficiency of activity of construction organizations were considered; analysis of number of indicators about activity of construction area was implemented; a group of organizations was chosen by using database “SPARK”; interrelationship between earnings and net profit was studied, comparative analysis between Ltd “Stroyregistr” and Closed Joint Stock Company “SEDO” is implemented. The main types of profit such as gross profit, profit on sales, before-tax profit and net profit were considered. It is worth noting that these types of profit are interrelated, since one category arises from the other depending on the income and expense items inherent in one or another type of profit. Analysis of the state of construction organizations involves the study of factors affecting their activity. For this purpose correlation and regression analysis was used in the work. Conclusion. To study the process of forming and using profits as an object of research, Ltd “Stroyregistr”, which operates in Moscow region, was chosen. As the competitor, Closed Joint Stock Company “SEDO”, which is also carrying out activity in Moscow region, was considered. During the analysis of these organizations, it was revealed that the activity of Ltd “Stroyregistr” is more stable and successful compared to Closed Joint Stock Company “SEDO”, which showed a sharp decline in financial indicators in 2016. However, the value of profitability on net profit in Ltd “Stroyregistr” is lower than the industry average value, which is associated with a low value of the net profit.As a result, the reasons that influenced the low value of net profit were identified. One of the main reasons is the high cost of the rendered services.